Decision making models in various fields of nursing - Kosicka, Bogumiła; Ksykiewicz-Dorota, Anna; Kulczycka, Kinga; Stychno, Ewa; Piasecka, Katarzyna; Drop, Bartłomiej (Polish Journal of Public Health, 2020)
Introduction. Identification of the process of decision making by nurses is a basis for better preparation of future nurses to an independent, and at the same time, effective decision making. This is related with the provision of high quality nursing services. Aim. The objective of the presented study was identification of the decision making models applied by Polish nurses, and investigation of the relationship between specificity of work in individual wards and the applied model of decision making. Material and methods. The research instrument was the Finnish 56-item questionnaire form examining decision making by nurses. This questionnaire was translated and adjusted to the Polish conditions, and its psychometric properties were confirmed concerning validity and reliability. The study covered nurses employed in conservative treatment wards (n=977), surgical wards (n=361) and intensive care units (n=293); a total number of 1631 Polish nurses employed in the hospitals was examined . Results. Analysis of data showed that nurses from various wards in the study applied four models of decision making: analytical, intuitive, analytical-intuitive, and intuitive-analytical. Selection of the model used was associated with the specificity of work in individual wards. Conclusions. The studies confirmed that during the process of decision making the nurses used both analytical and intuitive approaches, according to the type of ward and the specificity of the work of a nurse.